Synthesis of Nano-Crystalline LiNdxMn2-xO4 Powder by Novel Cam-Microwave Assisted Sol-Gel Method - K. Suryakala; R. Venckatesh (E-Journal of Chemistry)
With the advancement of nanotechnology, there is an interest in the replacement of conventional materials by nanomaterials. There is a reasonable chance that as the active mass of electrode for lithium batteries is comprised of smaller particles, they will perform better in terms of capacity, power, rate capability and stability. LiMn2O4 is inexpensive material but it shows rather poor cyclic performance. The electrochemical performance of spinel type LiMn2O4 has been effectively improved with doping of Nd the “bottom–up” approach of LiMn2O4 and LiNdx Mn2-xO4 (x = 0.1, 0.2, 0.3 and 0.4) synthesized by citric acid modified microwave assisted sol-gel method. LiMn2O4 has been synthesized from nitrates and acetates. Citric acid was added as a complexing agent and acryl amide acts as a gelling agent. This technique offers better homogeneity, preferred surface morphology, reduced heat-treatment conditions, sub-micron sized particles and better crystallinity. The structure and the electrochemical performances of the samples are characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, cyclic voltammetry and charge-discharge testing. XRD data shows both samples exhibit the same pure spinel phase. Nano crystalline LiNd0.3 Mn1.7 O4 sample has a smaller morphology including small particle size and the homogeneous particle distribution compared to the other compositions.